A CRITICAL ANALYSIS ON THE INTERDISCIPLINARY PERSPECTIVES ON THE INTERSECTION OF DEVICES IN RADIOLOGY AND PHYSICAL THERAPY - Khalid Sahal Salem Alsallum, mohammed hussainsalamlsloom, Abdulhadi awadhalmutairi MajedSahal Salem ALSallum, Abdulmohse maqboalalmutairi, Mohammed Abdullah Alhagri (Chelonian Research Foundation, 2023)
This article analyzes the crossing point and overlapping shapes of radiology gear in physical therapy. By investigating existing archives and methods, the study gives knowledge into the results, challenges, and openings that emerge from the integration of these exercises. Investigate how progress within the utilization of radiation therapy is affecting healthcare and article clarifies the integration of radiology and physical therapy, the joint utilization of progressed innovation, and its potential to move patients forward. The advancement of innovation in healthcare touches on vital subjects such as examination, conclusion, therapy, and innovation. From a basic viewpoint, this consideration points to pick up a more profound understanding of the integration of radiology gadgets and physical therapy by proposing earlier inquiries about headings, consequent, and clinical techniques to progress persistent results and advance well-being. Keywords: Devices, radiology, physical therapy, interdisciplinary collaboration, healthcare delivery, personalized care, clinical outcomes, technological advancements, patient-centered approach, integration, barriers, synergy, innovation, quality of life, paradigm shift.